Application of CT for the Study of Pathology of the Jaws - Tanaka, Tatsurou; Morimoto, Yasuhiro; Tanaka, Tatsurou; Kito, Shinji; Ishikawa, Ayataka; Kokuryo, Shinya; Yamamoto, Noriaki; Habu, Manabu; Miyamoto, Ikuya; Kodama, Masaaki; Matsumoto-Takeda, Shinobu; Oda, Masafumi; et al. (IntechOpen, 2011)
None